2020
DOI: 10.24940/theijhss/2020/v8/i5/hs2005-069
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Teacher-Student Relationships on Learners’ Loneliness in Single Gender and Co-educational Schools in Murang’a County, Kenya

Abstract: Influence of Teacher-Student Relationships on Learners' Loneliness in Single Gender and Coeducational Schools in Murang'a County, Kenya 1. Introduction There are concerns expressed by stakeholders in education regarding the influence of the teacher-student relationship on the loneliness levels among learners in schools in the world and Kenya in particular. Loneliness is believed to greatly impact on the school outcomes of the learners in schools especially in Murang'a in Kenya. Public schools in Kenya can eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Foremost amongst these issues is being away from family and adaptation problems, which are important enough to be discussed at Turkish Grand National Assembly (TGNA) (Eraslan, 2006). When examining the international literature, it is observed that boarding schools are mostly for adolescents, and prominent issues include mental health (Aisyaroh and Ediyono, 2023;Hopkins et al, 2023), psychological resilience (Langham et al, 2018;Redman-MacLaren et al,2017), loneliness (Baru, et al, 2020;Rudrum, 2020), and adaptation (Sri-Wahyuni and Barus, 2020;Su et al, 2019). Hence, there is a need for effective psychological guidance and counseling services to support the psychological and social development of the students at RBSs and help them with their emotional problems (Atli, 2018;Pavletic et al, 2016).…”
mentioning
confidence: 99%
“…Foremost amongst these issues is being away from family and adaptation problems, which are important enough to be discussed at Turkish Grand National Assembly (TGNA) (Eraslan, 2006). When examining the international literature, it is observed that boarding schools are mostly for adolescents, and prominent issues include mental health (Aisyaroh and Ediyono, 2023;Hopkins et al, 2023), psychological resilience (Langham et al, 2018;Redman-MacLaren et al,2017), loneliness (Baru, et al, 2020;Rudrum, 2020), and adaptation (Sri-Wahyuni and Barus, 2020;Su et al, 2019). Hence, there is a need for effective psychological guidance and counseling services to support the psychological and social development of the students at RBSs and help them with their emotional problems (Atli, 2018;Pavletic et al, 2016).…”
mentioning
confidence: 99%